'We're touching the topic, but we're not opening the book:' A grounded theory study of sibling relationships in young people with perinatally acquired HIV. (March 2022) - Deakin, Hannah; Frize, Graham; Foster, Caroline; Evangeli, Michael
HIV-related stressors affecting young adults with perinatally acquired HIV (PHIV+) and their siblings include parental and sibling ill-health and death, own ill-health, HIV disclosure, and stigma. Young people with PHIV+ typically share their HIV status with family members. We explored sibling relationships in young people with PHIV+. Ten participants (six females, 17–23 years old) with PHIV+ took part in a semi-structured interview, analysed using Grounded Theory. The data were condensed into three theoretical codes: (1) HIV disclosure in sibling relationship; (2) Patterns of communication about HIV between siblings; and (3) Patterns of coping and support in sibling relationship.